SOS hotline for women victims of discrimination at the workplace - Dobrosavljević-Grujić Ljiljana S. (Temida, 2004)
SOS hotline for women victims of discrimination at the workplace offers free legal assistance to women, whenever their labor rights are endangered. If the dispute cannot be resolved peacefully by mediation between employer and employees, female lawyer skilled for the labor law starts up judicial proceedings. Some characteristic cases of discrimination of women from the practice of SOS telephone, such as dismissal from the work, physical violence and sexual blackmail, are presented in the paper.